Developing a Differentiated Assessment Model for Teaching at the Right Level: Improving Quality of Inclusive Teaching in Elementary School - Muhajang, Tatang; Sukmanasa, Elly; Budiana, Sandi; Abdul Gani, Resyi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The main challenges are the lack of proper assessments by teachers of students' abilities in inclusive classrooms and the limited training to develop teachers' skills. This study aims to create a Teaching At the Right Level (TARL) differentiated assessment model to improve the quality of inclusive teaching in elementary schools. The method used was the ADDIE R&D model, where the research was conducted in 8 schools in the Tanah Sareal Bogor, with 105 teacher respondents and 37 children with special needs. The results showed that this model is believed to be useful for students with special needs. The assessment tool was validated by experts with an average score of 4.45 and 4.23, indicating excellent quality concerning clarity of purpose, importance of curriculum, and ability to detect students' strengths and limitations. The results showed that 86.5% of students felt helped in learning, 75.7% experienced increased understanding, and 83.8% felt more motivated. Furthermore, the model proved locally and universally relevant and has contributed significantly to developing a more adaptable and impactful inclusive education.